Game Tebak Gambar Sebagai Media Pembelajaran Untuk Anak Usia Dini - Andhika Mega Pradana; Ade Mubarok (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Many games are starting to appear that are less educational and less suitable to be played which have a bad impact on children, as well as the lack of parental supervision of children in excessive use of gadgets. the need for a media that can unite two elements, namely game play and learning, therefore an educational game application is made that uses construct 2 and coreldraw which serves as the interface design processor, objects, buttons, and players. This educational game raises the theme of introducing the names of animals in the form of pictures, which will later become an alternative learning that provides a more useful education, has a positive impact on children, and can reduce children playing games that are not suitable for their age. With this application, it provides broad insight to children about recognizing animal names and understanding them, and can fill children's free time which is usually spent just playing less useful games by playing and learning with this educational game application.